2018
DOI: 10.1055/s-0043-121737
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis as a prequel to very severe aplastic anemia

Abstract: Severe aplastic anemia is a rare and potentially life-threatening disease of the bone marrow often requiring allogeneic hematopoietic stem cell transplantation. Pathogenesis of the disease can vary and often remains enigmatic. Occasionally, severe aplastic anemia is associated with prior severe acute hepatitis. Differential diagnosis of acute non-viral hepatitis challenges the physician as pathogenesis remains unclear.We here present a case of a young patient presenting with acute hepatitis followed by severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Experimentally infected animals, with chronic and acute hepatitis E, presented incipient histological signs, suggesting BM hyperactivation and dysfunction, characterized by vacuolization in endosteal cells, with some fields suggesting displasic focal disease. Medical research studies described severe aplastic anemia in association with parvovirus B19 (B19V), hepatitis A virus (HAV) and hepatitis C virus (HCV) infections [ 32 34 ]. Besides, recent studies described association between endosteal niche and loss of hematopoiesis homeostasis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally infected animals, with chronic and acute hepatitis E, presented incipient histological signs, suggesting BM hyperactivation and dysfunction, characterized by vacuolization in endosteal cells, with some fields suggesting displasic focal disease. Medical research studies described severe aplastic anemia in association with parvovirus B19 (B19V), hepatitis A virus (HAV) and hepatitis C virus (HCV) infections [ 32 34 ]. Besides, recent studies described association between endosteal niche and loss of hematopoiesis homeostasis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 213 children, Führer et al reported that the underlying etiology of aplastic anemia was 80% idiopathic, 9% post‐hepatitis, 7% other post‐viral, and 4% related to drugs and toxins 39 . Hepatitis‐associated aplastic anemia (HAAA) has been reported to constitute anywhere from 2% to 21% of SAA cases, depending upon the geographic region and study 37,38,40–44 . On rare occasions, hepatitis viruses including A, B, C, D, E and G, as well as parvovirus, cytomegalovirus (CMV), and Epstein–Barr virus (EBV), have been associated with the development of SAA 37,42,45–49 .…”
Section: Required Observationsmentioning
confidence: 99%
“…39 Hepatitis-associated aplastic anemia (HAAA) has been reported to constitute anywhere from 2% to 21% of SAA cases, depending upon the geographic region and study. 37,38,[40][41][42][43][44] On rare occasions, hepatitis viruses including A, B, C, D, E and G, as well as parvovirus, cytomegalovirus (CMV), and Epstein-Barr virus (EBV), have been associated with the development of SAA. 37,42,[45][46][47][48][49] However, in most cases of HAAA a cause cannot be identified, and the time interval between onset of hepatitis and a diagnosis of SAA can vary from 6 months to a concurrent presentation.…”
Section: Fetal Hemoglobin Evaluationmentioning
confidence: 99%
“…W większości opisywanych przypadków nie zaobserwowano obecności wirusów hepatotropowych [7][8][9][10][11][12][13][14][15][16]. Wśród [15].…”
Section: Etiologia Uszkodzenia Wątrobyunclassified